STATISTICAL CONVERGENCE OF DOUBLE SEQUENCES IN NEUTROSOPHIC 2-NORMED SPACES - Rahul Mondal; Nesar Hossain (Ural Mathematical Journal)
In this paper, we have studied the notion of statistical convergence for double sequences in neutrosophic 2-normed spaces. Also, we have defined statistically Cauchy double sequences and statistically completeness for double sequences and investigated some interesting results in connection with neutrosophic 2-normed space.